Carbon sequestration benefits of the grain for Green Program in the hilly red soil region of southern China - Xiaoqian Hu; Zhongwu Li; Jia Chen; Xiaodong Nie; Junyu Liu; Lingxia Wang; Ke Ning (International Soil and Water Conservation Research, 2021)
Soil erosion disturbs not only the global carbon cycle, but it is a complex environmental problem. Revegetation could reduce carbon emission by controlling soil erosion and increase carbon sequestration and accumulation by fixing carbon in vegetation and soil. The Grain for Green Program (GFGP) of China is the largest ecological restoration program in the world closely related to land-use/land-cover change (LUCC). Systematically assessing the carbon sequestration benefit of GFGP is crucial for a better understanding of the effects of implementing GFGP and providing reasonable vegetation management. Therefore, we selected the hilly red soil region (HRSR) of southern China as a study area, which is one of the main ecologically vulnerable areas in China. We assessed the carbon sequestration in the GFGP area of the HRSR using the InVEST (Integrated Valuation of Environmental Services and Tradeoffs) model based on land-use/land-cover datasets during 2000–2015. Our results show that implementing GFGP is conducive to the enhancement of carbon sequestration services. Total carbon sequestration showed an increasing trend at a rate of 15.43% from 2000 to 2015. The most significant change mainly happened in Hunan Province with the shortest implementation time. The carbon sequestration of each carbon pool (namely aboveground biomass, belowground biomass, soil, and dead organic matter) also increased slightly. Additionally, for carbon sequestration, unused land converted to forest land is the most effective LUCC. This study can provide scientific support for the management and implementation of GFGP in the HRSR of China.